Pressure-melting of ice - Nordell, Bo (Luleå tekniska universitet, Arkitektur och vatten, 1989)
The pressure-melting curve of ice is often found in literature deling with ice problems. This curve originates form the eexcellent experimental works of G. Tammann (1903) and P.V. Bridgman (1912). The method used means that ice at constant temperature is submitted to an external pressure. When increasing the pressure a sudden volume change occurs, the pressure-melting point is reached. Results from their works are summarized in this paper. An alternative experimental method was used in this study. Water is confined in a filled up pressure tank. The water is then cooled from an initial temerature of 0°C. The ice formed creates a pressure incerase in the ice-water mixture. At any temperature a corresponding pressure occurs at phase equilibrium. The temperature and the pressure are measured in the ice-water mixture. The results are in good agreement with earlier measurements. The method used, which is easy to handle even with this prototype equipment, should be more accurate than the old method since one possible source of error (the external pressure) is eliminated. The method could be used for other substances than pure water. Godkänd; 1989; 20070906 (pafi)